Gender and Patient Preferences: Unraveling the Decision-Making Process for Blepharoplasty Among Males and Females - Al-Dossary SK (Patient Preference and Adherence)
Saif Khuzaim Al-Dossary Department of Surgery, College of Medicine, King Faisal University, Al-Ahsa, Saudi ArabiaCorrespondence: Saif Khuzaim Al-Dossary, Email Saldossari@kfu.edu.saBackground: Blepharoplasty is a popular facial cosmetic surgery, but research on how gender may influence motivations for this eyelid procedure remains limited. Understanding differences can improve patient counseling.Objective: This study examined gender variances in key factors driving blepharoplasty decisions.Methods: Medical records of 100 blepharoplasty patients (50 males, 50 females) were analyzed for demographics and patient-reported reasons underlying surgery choice. Face-to-face surveys further assessed satisfaction and experiences.Results: Social embarrassment concerns declined with patient age but were more commonly reported by men (63.6%) than women (36.4%). Looking younger was overwhelmingly a female motivation (89.3% women vs 10.7% men), especially prevalent among those ages 30– 35 (78.6%). Eye heaviness was a shared concern among this age bracket (57.1%), suggesting functional factors. Marriage considerations, though uncommon (3%), remained relevant to younger subgroups (66.7% ages 25– 30).Conclusion: Key factors showed both gender divergences and convergences, with men emphasizing functional/social issues and women cosmetic youthfulness. Understanding nuances can help surgeons tailor blepharoplasty patient education.Keywords: blepharoplasty, motivation, gender differences, age, function, cosmetic